Intraoral appliances for in situ oral biofilm growth: a systematic review. Issue 1 (1st January 2019) - Abdullah, Nizam; Al-Marzooq, Farah; Mohamad, Suharni; Abd Rahman, Normastura; Chi Ngo, Hien; Perera Samaranayake, Lakshman
ABSTRACT: Background : Oral biofilms are the root cause of major oral diseases. As in vitro biofilms are not representative of the intraoral milieu, various devices have been manufactured over the years to develop Appliance Grown Oral Biofilm (AGOB). Objective : To review various intraoral appliances used to develop AGOB for microbiological analysis, and to judge the optimal means for such analyses. Design : Four databases (PubMed, Science Direct, Scopus and Medline) were searched by two independent reviewers, and articles featuring the key words 'device' OR 'splint' OR 'appliance'; 'Oral biofilm' OR 'dental plaque'; ' in vivo ' OR ' in situ '; 'Microbiology' OR 'Bacteria' OR 'microbiome'; were included. The standard Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) were adopted for data gathering. Results : Of the 517 articles which met the initial inclusion criteria, 24 were deemed eligible for review. The age of the AGOB, sampled at various intervals, ranged from 30 min to 28 days. The most commonly used microbiome analytical methods were fluorescence microscopy, total cell count using conventional, and molecular tools including Next Generation Sequencing (NGS) platforms. Conclusions : No uniformly superior method for collecting AGOB could be discerned. NGS platforms are preferable for AGOB analyses.